2017
DOI: 10.1093/glycob/cwx065
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 binds to O-glycans on protein disulfide isomerase

Abstract: Changes in the T cell surface redox environment regulate critical cell functions, such as cell migration, viral entry and cytokine production. Cell surface protein disulfide isomerase (PDI) contributes to the regulation of T cell surface redox status. Cell surface PDI can be released into the extracellular milieu or can be internalized by T cells. We have found that galectin-9, a soluble lectin expressed by T cells, endothelial cells and dendritic cells, binds to and retains PDI on the cell surface. While endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 76 publications
0
27
0
Order By: Relevance
“…It renders CD4 + T cells less susceptible to HIV infection via induction of the host restriction factor cyclin-dependent kinase inhibitor 1 (p 21) (42). It can also increase HIV entry by inducing the CD4 + T cell-surface concentration of protein disulfide isomerase (PDI) (43). We have previously shown that the endogenous levels of Gal-9 are induced after HIV infection and that these levels do not return to normal levels after ART suppression (20).…”
Section: Discussionmentioning
confidence: 99%
“…It renders CD4 + T cells less susceptible to HIV infection via induction of the host restriction factor cyclin-dependent kinase inhibitor 1 (p 21) (42). It can also increase HIV entry by inducing the CD4 + T cell-surface concentration of protein disulfide isomerase (PDI) (43). We have previously shown that the endogenous levels of Gal-9 are induced after HIV infection and that these levels do not return to normal levels after ART suppression (20).…”
Section: Discussionmentioning
confidence: 99%
“…Gal-9 also binds to protein disulfide isomerase (PDI), a cell surface enzyme. This binding increases PDI retention on the surface of CD4 + Th2 cells and alters the redox status of the plasma membrane; consequently, Gal-9 increases cell migration through the extracellular matrix via β 3 integrin [ 33 , 34 ].…”
Section: Galectin-9 Molecular and Cellular Biologymentioning
confidence: 99%
“…Our finding that somite cell surface PDI (csPDI) binds PNA, and is lactose-elutable from immobilized PNA, indicates that this form of PDI is O-glycosylated. This is supported by the observation that csPDI expressed by Jurkat T cells, immortalized from human T cell leukaemia, also possesses PNA-binding O-glycans, the elongation of which can be blocked experimentally 21,22 . In addition, using a sensitive fluorescent reductase assay 23 we found that commercially purified (bovine liver) PDI does not bind to PNA-agarose, indicating that somite csPDI has an affinity for PNA based on its glycosylation state ( Figure 1-figure supplement 1b ).…”
Section: Resultsmentioning
confidence: 79%